INTERVENSI NON-FARMAKOLOGIS UNTUK MENGURANGI KECEMASAN PASIEN KANKER YANG MENJALANI KEMOTERAPI: A SCOPING REVIEW - Agung Subakti Nuzulullail; Halfie Zaqiyah Gusti Puspitasari; Dwina Oktavia Deli (CV. Denasya Smart Publisher, 2026)
Anxiety is a psychological response often experienced by cancer patients undergoing chemotherapy and can affect the patient's physiological condition and comfort. Various non-pharmacological therapies are used as a supportive approach to help reduce anxiety during cancer therapy. This scoping review aims to map the types of non-pharmacological interventions used, the duration of implementation, the measurement tools used, and the reported effects on cancer patients undergoing chemotherapy. The scoping review design refers to the Arksey & O'Maley framework in two databases, namely PubMed, Science Direct, and Google Scholar grey literature, and is adjusted to PICO. The inclusion criteria for this study included original research articles written in English, published between 2010 and 2025 to ensure the latest scientific evidence, and specifically discussing non-pharmacological therapies in reducing anxiety in cancer patients undergoing chemotherapy. Secondary data-based studies, protocol articles, preliminary studies, and books or book chapters were excluded from the review. A total of 10 articles were synthesized, and the interventions found included group music therapy, listening to instrumental music during radiotherapy, traditional Thai massage, aromatherapy massage with lavender, zikir therapy, and interventions based on reading the Qur'an and music. Anxiety was measured using psychological instruments such as Beck Anxiety Inventory-Cancer (BAI-C), Distress Thermometer (DT), Brief Symptom Rating Scale-5 (BSRS-5), State-Trait Anxiety Inventory (STAI), General Comfort Questionnaire (GCQ), dan Visual Analogue Scale (VAS), as well as physiological parameters such as blood pressure, pulse rate, respiration, and oxygen saturation. The results of the study showed a decrease in anxiety, stress, and distress, an increase in comfort and well-being, and changes in vital signs after the intervention was given. These findings indicate that non-pharmacological therapy was applied using various methods and durations and assessed using psychological and physiological instruments, with reported effects on patients' anxiety levels during cancer therapy.